THE DETAILED PRIORITY OF INTERNATIONAL FREIGHT EXPRESSES IN THE OVERLAPPING SECTION OF RFC 7 AND RFC 9 KOLÍN – CHOCEŇ - Přemysl Šrámek; Tatiana Molková (Acta Polytechnica CTU Proceedings, 2017)
The main goal of this article is to research the optimal priority of international freight expresses, especially on European freight corridors. This article shows this problem in the context in the overlapping section of RFC 7 and RFC 9 Kolín – Chocen. There is solved changing priority of freight expresses in detail, whereas other train priorities are the same.